Establishment of User Requirements Handbook based on the Situational Awareness Knowledge for Malaysian Military Observers - Su Emi Yusnita Wan Yusof, Wan; Zakaria, Omar; Zainol, Zuraini (International Journal of Engineering and Technology, 2018)
Up to this moment, there are not many studies have been carried out to collect tacit knowledge in the area of peace keeping which are related to the situational awareness. The problems arise when the military observers have come to the end of their service in which they will bring along the knowledge. Furthermore, these issues become crucial when the knowledge is not fully transferred to the new person in charge. Therefore, there is a need to extract the tacit knowledge in a formal approach and come out with a user requirement handbook. Our main framework will be using the combination of two models: Nonaka and Endsley. This framework can assist our research in terms of collecting and transforming appropriate tacit knowledge and documented as a user requirement handbook. By that, this paper is aiming to show some of the results obtained from this study. This finding will then be generated as a user requirement handbook.Â